Translation and cross-cultural adaptation of the Hypertension Knowledge-Level Scale for use in Brazil - Juliana Perez Arthur; Maria de Fátima Mantovani; Maria Isabel Raimondo Ferraz; Ângela Taís Mattei; Luciana Puchalski Kalinke; Roselene de Campos Corpolato (Universidade de São Paulo, 2018)
ABSTRACT Objective: to make the translation, cross-cultural adaption and content and face validation of the Hypertension Knowledge-Level Scale for use in Brazil. Methods: methodological research carried out in six stages: translation, synthesis, back-translation, expert committee's assessment, pre-test and validation. Validation was performed through the Delphi technique in two rounds. The participants were two translators and two back-translators, eight professionals in the expert committee, 40 adult participants in the pre-test, 35 experts in the first validation round and 28 in the second validation round. Data analysis included Cronbach's alpha, content validity index and one-tailed t-test. Results: the translation and cross-cultural adaptation allowed for language adjustments so that the items were comprehensible and suitable for use in Brazil. The content validity index of the Brazilian version of Hypertension Knowledge-Level Scale was 0.96 and Cronbach's alpha was 0.92. Conclusions: the scale was translated, cross-culturally adapted to Brazilian Portuguese, had its content and face validated and proved reliable to evaluate the knowledge of adults about hypertension.